Perubahan Penggunaan Lahan dan Kesesuaiannya Terhadap Pola Ruang di Kecamatan Payangan, Kabupaten Gianyar, Bali - Putra, I Putu Bisma; Mahendra, Made Sudiana; As-syakur, Abd. Rahman (Bumi Lestari; Vol 25 No 1 (2025), 2025)
Payangan District is inseparable from the phenomenon of land use change, as human intervention in natural and man-made resources with the aim of meeting spiritual and material needs. Land use conversion has an impact on the mismatch between land use and its intended use plan. This study aims to analyze land use changes from 2016 to 2023 and assess the suitability of land use in 2023 with the spatial pattern of the Gianyar Regency Spatial Planning in Payangan District. The study applied the analysis and spatial survey method, the overlay method produced a map of land use changes and the suitability of land use in 2023 with the Gianyar Regency Spatial Plan (RTRW) in Payangan District. The results showed that Payangan District experienced a land use conversion of 1,146.84 ha by 15.58%. The use of garden land experienced the largest land use change of 401.27 ha, while the use of organizational land experienced the smallest change of 36.37 ha. The results of the suitability of land use in 2023 against the Regional Spatial Plan (RTRW) of Gianyar Regency in Payangan District 2012-2032 show that the use of suitable land covers an area of 2,230.41 ha amounting to 30.32%, while the use of unsuitable land covers an area of 5,128.25 ha amounting to 69.68%.